Evaluation of Morinda citrifolia leaf extract against Phytophthora palmivora in controlling stem canker on durian (Durio zibethinus) - Nor Dalila Nor Danial; Norhayu Asib; Tosiah Sadi; Siti Izera Ismail (Penerbit Universiti Kebangsaan Malaysia, 2025)
Durian is an economically important crop in Malaysia and has been identified as a new source of agricultural wealth valued at USD 1.58 billion. However, Phytophthora palmivora has been reported in all areas where durian has been planted and continues to pose a significant challenge for durian growers. The crop losses and control costs were estimated at 11.7% in 2020. Durian farmers have applied oomycete fungicides for more than 20 years to control stem canker, and extensive use of fungicides has resulted in the development of resistant Phytophthora isolates. This study aimed to evaluate four different leaf crude extracts of mengkudu (Morinda citrifolia) extracted using methanol, acetone, ethyl acetate, and hexane solvents against P. palmivora. GC-MS analysis of M. citrifolia leaves crude extract revealed the presence of squalene. In-vitro screening of the M. citrifolia plant extracts, the crude extracts of acetone and ethyl acetate revealed effective concentration 50% (EC50) values of 36.115 and 38.095 mg/mL, respectively. PDA supplemented with acetone solvent at 60 mg/mL altered the morphology and inhibited the mycelial growth of P. palmivora. In an in-vivo bioassay screening level, treated plants of M. citrifolia extract of ethyl acetate 76 mg/mL had a lesion growth of 30.24 mm on the stem. This treatment was not significantly different from the control positive treatment applied with Ridomil fungicide. Morinda citrifolia leaf extracts using methanol, acetone, and ethyl acetate revealed it could be used as an alternative biocontrol agent for foliar spraying to reduce disease severity in durian seedlings against P. palmivora.